Batu Lobang: Potensi Wisata Bahari Berkelanjutan di Desa Banjarsari, Pulau Enggano - Akin Kristianto; Erza efrilian; Thiya Pisces; Nasywah Sofia Al Jannah; Eko Nofridiansyah (CV. ITTC INDONESIA, 2026)
The Student Community Service Program (KKN) is a form of community service undertaken by students to directly apply their academic knowledge, skills, and experience within a community setting. KKN activities aim not only to assist the community in addressing various challenges but also to provide students with an opportunity to identify and develop a region's local potential. The KKN program in Banjarsari Village, Enggano Island (North Bengkulu Regency), was conducted to identify the marine tourism potential of Batu Lobang a significant natural asset. Batu Lobang features unique natural characteristics, specifically a natural rock formation resembling a gateway with a central opening. Beyond its distinctive rock structure, the area boasts a lagoon with clear water and a pristine natural landscape. The methodology employed for this initiative involved direct observation via field visits, utilizing small boats for transportation to the site. During the activity, students collaborated with local residents who served as boat operators, assisting with the journey to the Batu Lobang area.